Product configuration for photovoltaic systems in developing countries - Oyeyiola, Francis; Ndzibah, Emmanuel (Green Publishers, 2019)
Demand and supply of electricity have always been problematic in developing economies. Poor infrastructure because of weak government policies has compounded the problem thus making it difficult for businesses to operate uninterrupted. As a result, households and businesses have no choice than to take matters in their own hands. The paper uses Ghana (a West African country) as the focus of study. The main objective is to develop various solar photovoltaic (solar PV) configurations for households and businesses in developing economies. The proposed research question is set as, ‘how can product configuration support reduction and improvement of the energy predicament in developing economies?’ The possibilities include standalone, backup or hybrid systems with a focus on off grid solutions. As a limitation, this paper confines its choices to backup systems because of the current distribution of electricity in Ghana. The empirical background provides insight into existing energy condition and the renewable energy plans in Ghana [6,11,17,18]. The method applied in this paper includes focus group study and a survey. The focus group session utilized some African students living in Finland while the main survey utilized a sample frame in Ghana to arrive at the desired conclusion. Some 102 respondents answered questionnaire via Google Form. From the outcome, the most common areas of use for solar PV included lighting, some household and office appliances with varied configurations. The study confirms the inadequate supply of electricity in Ghana and proposed solar PV systems as a viable alternative.
Keywords: solar photovoltaic systems; product configuration; developing economies; Ghana; fi=Tuotantotalous|en=Industrial Management|